Efforts of the Government of the Republic of Indonesia in Creating a Sense of Security for the Community and State from the Threat of Terrorism - Bangbang Surono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The threat of terrorism poses a serious challenge to national security and communities around the world, including Indonesia. The Government of the Republic of Indonesia has taken various strategic steps to counter and prevent acts of terrorism to create a sense of security for the people and the integrity of the country. This study aims to describe the government's efforts in responding to the threat of terrorism as well as evaluating the effectiveness of the measures that have been taken. The Government of Indonesia, through its security forces and related agencies, has enhanced international cooperation for the exchange of intelligence information to detect and prevent potential terror attacks. In addition, community empowerment in identifying signs of radicalism and terrorism is also the government's main focus. Deradicalization and rehabilitation programs have been strengthened as part of prevention strategies, involving religious leaders, educators, and civil society. Through an in-depth analysis of such measures, the study aims to provide a comprehensive picture of the government's efforts to create a sense of security from the threat of terrorism. The results of the study are expected to contribute to a further understanding of the dynamics of terrorism prevention and provide policy advice to strengthen Indonesia's national security